Model Supervisi Akademik Partisipatif: Kerangka Konseptual dan Pedoman Implementasi Budaya Reflektif-Kolaboratif - Aan Anengsih; Mila Nuroniyah; Supardi; Agus Gunawan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study aims to examine and formulate a Participatory Academic Supervision Model as a strategic approach to building a reflective and collaborative culture in schools. The main focus is to explore the concepts, principles, and practices of academic supervision that emphasize active participation among principals, teachers, and supervisors in improving the quality of learning. This research employs the library research method, analyzing various scholarly sources such as books, journals, and previous studies related to academic supervision, professional reflection, and educational collaboration. The data were analyzed descriptively and critically to synthesize theoretical ideas and empirical findings supporting the development of a participatory supervision model. The results indicate that participatory academic supervision strengthens professional relationships through reflective dialogue, peer collaboration, and continuous constructive feedback. This model promotes a school culture that values openness, continuous learning, and pedagogical innovation. The study concludes that participatory academic supervision is an effective approach to fostering a reflective, collaborative, and quality-oriented educational ecosystem.